How to guide learners' processing of multimedia lessons with pedagogical agents. (April 2023) - Li, Wenjing; Wang, Fuxing; Mayer, Richard E.
Abstract: Two experiments examined the effects of a pedagogical agent's (PA's) pointing gestures, eye gaze, and eye contact on learning processes (measured by learners' eye fixations on relevant elements) and learning outcomes (as measured by retention and transfer test scores) with a multimedia lesson on neural transmission. In Experiment 1, having the PA look at and point to relevant elements as she lectured led to more eye fixations on the relevant portion of the graphic and better retention and transfer test scores. Keeping eye contact with learners tended to improve retention test scores and increased their eye fixations on relevant elements when the PA also looked at and pointed to the graphic. In Experiment 2, the PA's pointing gestures as a stand-alone feature caused better retention test scores and more fixations on relevant elements of the graphic, but eye gaze direction did not. These findings help extend the embodiment principle. Highlights: Eye gaze and pointing by PAs caused more eye fixations on relevant elements. Eye gaze and pointing by PAs caused better retention and transfer scores. Eye contact of PAs towards learners tended to result in better retention scores. Eye gaze toward the graphic did not improve learning.